2002
DOI: 10.1002/1521-3951(200201)229:1<513::aid-pssb513>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Deep‐Level Transient Spectroscopy and Cathodoluminescence of CdSe/ZnSe QD Structures Grown on GaAs(100) by MBE

Abstract: b) P.N. Lebedev Physical Institute, RAS, 53 Leninsky Pr., CdSe/ZnSe structures grown on n þ -GaAs(100) by molecular beam epitaxy were studied by methods of deep-level transient spectroscopy (DLTS) and cathodoluminescence (CL). In DLTS measurements, an unusual dependence of the activation energy for electron emission from CdSe layer levels on filling conditions was observed. This dependence was explained on basis of the interaction between electron charge in CdSe quantum dots (QD) and charged deep levels placed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Photoluminescence (PL) and CL investigations performed in these materials showed the appearance of luminescence bands at energies higher than the bulk band gap. In particular, Yamakawa et al 8 have reported a broad luminescence band centered at 2.49 eV in CdSe quantum dots of 15-40 nm in size grown by MBE, and Litvinov et al 17 have found similar bands peaked at 2.6 eV in quantum dots grown by the same technique. The emergence of these emissions in the visible range has been explained by quantum confinement effects.…”
Section: Resultsmentioning
confidence: 99%
“…Photoluminescence (PL) and CL investigations performed in these materials showed the appearance of luminescence bands at energies higher than the bulk band gap. In particular, Yamakawa et al 8 have reported a broad luminescence band centered at 2.49 eV in CdSe quantum dots of 15-40 nm in size grown by MBE, and Litvinov et al 17 have found similar bands peaked at 2.6 eV in quantum dots grown by the same technique. The emergence of these emissions in the visible range has been explained by quantum confinement effects.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, the cation vacancy formation features A 2 B 6 semiconductors, and they cause a series of absorption and radiation bands in these materials [11]. Secondly, the deep traps for electrons were found in CdSe/ ZnSe structures with QDs by DLTS method [12]. And thirdly, it should be noted that in the case of the high density of QDs, when the distances between the islands are comparable with their size (for 1.5 ML the density of islands is ~ 10 11 cm 2 , and the average distance between them is 15-20 nm [1]), an elastic interaction between the islands becomes essential as a result of penetration of nonuniform strain field caused by the QDs into the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…To estimate a potential barrier height for electron capture in QDs we explored the dependence of the E1 and E1 * amplitudes for structure No. 281 on the relaxation time as described in [4,5,13]. These examinations allow us to determine a temperature dependence of capture cross section σ (T ) as [4]:…”
Section: Dlts Studymentioning
confidence: 99%